(untitled) (Web of Teachers: Inderscience Research, 2025)
One of the most relevant skills that modern education provides is to improve the critical thinking skills of school-age students. Even until recently, the term "critical thinking" was understood as a critical approach to a particular event, a negative-negative opinion. Currently, the International Assessment Criteria for Assessment of Knowledge and Skills (PISA,TIMMS) also require critical thinking skills from students. This, in turn, requires science teachers to regularly use exercises and assignments that develop critical thinking in the classroom. This article discusses the theories of foreign scholars on critical thinking and some problematic situations that hinder this in exercises, assignments and lessons that develop critical thinking in English language lessons.